THE BAURU SUPERSEQUENCE (CRETACEOUS OF THE PARANÁ BASIN): STRATIGRAPHIC REVISION BASED ON RECENT PALEONTOLOGICAL DATA - Arai, Mitsuru [UNESP]; Dias-Brito, Dimas [UNESP] (Derbyana, 2023)
The Bauru Supersequence (BS), Paraná Basin, refers to a Cretaceous continental sedimentary section encompassing the Caiuá and Bauru groups. Surface and subsurface studies have subdivided the BS into several lithostratigraphic units. However, the stratigraphic framework of the BS remains unstable and there is, moreover, a precarious bridge between lithostratigraphy and biochronology, with the latter marked by conflicts arising from taxonomic divergences. We discuss this problem in light of recent key palynological data tied to the reference Cretaceous biochronology applied to coastal basins in Brazil and other paleontological information. The Caiuá Group is here sustained as the Aptian–Albian. The Bauru Group, which has fluvial sediments of the Santo Anastácio Formation (Coniacian?) at its base, encompasses the Adamantina, Araçatuba, Uberaba, São Carlos, Itaqueri, Marília, and Serra da Galga formations in its main lithic body. Palynological studies have identified upper Santonian and lower Campanian sediments in the São Carlos and Araçatuba formations, respectively, whereas micropaleontology of charophytes and ostracods has indicated Maastrichtian (upper Maastrichtian?) strata in the Serra da Galga Formation. The combination of these data with the stratigraphic-spatial arrangement of the units allows us to infer a late Santonian to early Campanian age for the Adamantina/Uberaba formations and a Maastrichtian (late Maastrichtian?) age for the Marília and Serra da Galga formations. It is not ruled out that older Santonian or even pre-Santonian strata compose the Adamantina/Araçatuba formations. The Itaqueri Formation, certainly post-Santonian, is here speculatively associated with the lower to middle Campanian. Five erosional unconformities, delimiting four sequences, are associated with the BS: the base surface, Pre-Caiuá, the top of the Caiuá Group, and the tops of the Santo Anastácio, Adamantina/Uberaba/Itaqueri, and Marília/Serra da Galga formations. The temporal gaps between these units are uncertain due to imprecise dating of the Santo Anastácio unit. The maximum pre-Marília/Serra da Galga hiatus would involve the mid-Campanian to early Maastrichtian time interval.
SUPERSEQUÊNCIA BAURU (CRETÁCEO DA BACIA DO PARANÁ): REVISÃO ESTRATIGRÁFICA COM BASE EM DADOS PALEONTOLÓGICOS RECENTES
Keywords: Biostratigraphy; Brazil; Chronostratigraphy; Cretaceous; Lithostratigraphy